Syntheses, Crystal Structures and Physical Properties of Chromium and Rhodium Hydrogarnets Ca3[Cr(OH)6]2, Sr3[Cr(OH)6]2and Sr3[Rh(OH)6]2 - Albrecht, Ralf; Hunger, Jens; Doert, Thomas; Ruck, Michael (European Journal of Inorganic Chemistry, 2019)
The hydrogarnets Ca 3 [Cr(OH) 6 ] 2 , Sr 3 [Cr(OH) 6 ] 2 and Sr 3 [Rh(OH) 6 ] 2 were synthesized under hydroflux condition at about 200 °C. The starting materials Ca(NO 3 ) 2 ·6H 2 O, Sr(NO 3 ) 2 , Cr(NO 3 ) 3 ·9H 2 O and RhI 3 were reacted in mixtures of water and potassium hydroxide with molar ratios between 1.2:1 and 3:1. The structures and thermal properties of these hydrogarnets were studied by X-ray diffraction, thermal analysis, electron microscopy as well as infrared and UV/Vis spectroscopy. Low temperature single-crystal diffraction measurements revealed katoite-like structures, in which the tetrahedrally coordinated metal positions of the garnet are unoccupied and hydroxide ions replace the oxide anions for charge compensation. IR spectroscopy confirmed the presence of hydroxide groups, which form weak hydrogen bonds. The thermal decomposition of Ca 3 [Cr III (OH) 6 ] 2 first yields CaCr VI O 4 and CaO at 314 °C, which then react to Ca 3 (Cr V O 4 ) 2 at 823 °C. The decomposition of Sr 3 [Cr(OH) 6 ] 2 proceeds similarly in the first step but results in the mixed valent compound Sr 2.67 (Cr V O 4 ) 1.33 (Cr VI O 4 ) 0.67 at 730 °C. The decomposition of Sr 3 [Rh(OH) 6 ] 2 under the same conditions results in Sr 10.5 Rh III 3 Rh IV 4.5 O 24 .
CRIS-Team Scopus Importer:2022-04-14
Keywords: Crystal structure; Hydrogarnet; Single compound precursor; Spectroscopy; Thermal decomposition